2017
DOI: 10.1007/398_2017_10
|View full text |Cite
|
Sign up to set email alerts
|

How to Adapt Chemical Risk Assessment for Unconventional Hydrocarbon Extraction Related to the Water System

Abstract: We identify uncertainties and knowledge gaps of chemical risk assessment related to unconventional drillings and propose adaptations. We discuss how chemical risk assessment in the context of unconventional oil and gas (UO&G) activities differs from conventional chemical risk assessment and the implications for existing legislation. A UO&G suspect list of 1,386 chemicals that might be expected in the UO&G water samples was prepared which can be used for LC-HRMS suspect screening. We actualize information on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 129 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…Updates have been suggested for S17 KEMIMARKET [68], S28 EUBIOCIDES [196] with information from ECHA [273], S34 EXPOSOMEXPL [165,166] with new data from [274] plus new microbial metabolites [275,276] and S75 CyanoMetDB [118,119] (next release due early 2023). Suggestions for new contributions include a list of endocrine disruptors within the activities of PARC, the Proposition 65 (Prop-65) list of chemicals from the California EPA [277], Phenol-Explorer [278][279][280], the Database on Migrating and Extractable Food Contact Chemicals (FCCmigex) [281], and finally a shale gas suspect list [282] that has been applied in other studies: [283,284] and will fill a long-identified gap with respect to fracking-related content.…”
Section: Future Updates: New Submissionsmentioning
confidence: 99%
“…Updates have been suggested for S17 KEMIMARKET [68], S28 EUBIOCIDES [196] with information from ECHA [273], S34 EXPOSOMEXPL [165,166] with new data from [274] plus new microbial metabolites [275,276] and S75 CyanoMetDB [118,119] (next release due early 2023). Suggestions for new contributions include a list of endocrine disruptors within the activities of PARC, the Proposition 65 (Prop-65) list of chemicals from the California EPA [277], Phenol-Explorer [278][279][280], the Database on Migrating and Extractable Food Contact Chemicals (FCCmigex) [281], and finally a shale gas suspect list [282] that has been applied in other studies: [283,284] and will fill a long-identified gap with respect to fracking-related content.…”
Section: Future Updates: New Submissionsmentioning
confidence: 99%
“…For every model in the ensemble, we simulated contamination events by releasing particles at UOG source locations (well pads) and tracking the pathways where the contaminants were transported by groundwater flow. The approach focuses on contaminant release mechanisms at well pads as these have been demonstrated to be the most likely pathway for environmental release of UOG contaminants and does not account for possible mechanisms away from well pads that have lower probabilities, such as roadside truck spills (Faber et al., 2019 ; Rozell & Reaven, 2012 ; Shanafield et al., 2019 ). GWV, defined as the likelihood for contaminants from UOG to reach specified locations in the domain, was calculated for each grid cell as the proportion of models in the ensemble where particle tracks intersected that grid cell.…”
Section: Methodsmentioning
confidence: 99%
“…Practices that intentionally discharge produced water to the environment have the potential to increase risks to human health and the environment by introducing a new exposure pathway to an understudied wastewater ( Faber et al, 2019 ). To date, the majority of studies on chemical hazards associated with onshore produced water have focused on hydraulic fracturing chemicals used in the stimulation process rather than the produced water generated by it and other development practices ( Colborn et al, 2011 ; Elsner and Hoelzer, 2016 ; Gordalla et al, 2013 ; Rogers et al, 2015 ; Yost et al, 2016a , 2017 ).…”
Section: Introductionmentioning
confidence: 99%